Graphite felt as a versatile electrode material: Properties, reaction environment, performance and applications. (20th December 2017) - Castañeda, Locksley F.; Walsh, Frank C.; Nava, José L.; Ponce de León, Carlos
Abstract: Carbon electrode materials have been extensively studied due to their diverse structure and chemistry which has enabled diverse applications. The thermal synthesis of graphite felt (GF) from polymeric precursors and the physical and electrochemical properties of flexible graphite felts are summarised. In electrochemical flow cells, the three-dimensional structure of GF as an electrode material counteracts the limitations of the low conversion and space–time yield possible with two-dimensional electrodes. The high volumetric area of GF facilitates the treatment of dilute solutions. The physical structure of GF enables it to act as a turbulence promoter, enhancing the hydrodynamics and mass transport rates in electrochemical systems. The electrochemical applications of GF in electroanalysis, electrosynthesis, electrochemical advanced oxidation processes, redox flow batteries, fuel cells, and metal ion removal are illustrated by examples. The characterisation of reaction environment, including non-ideal electrolyte flow, mass transport rates, fluid pressure drop, current and potential distributions of GF in electrochemical reactors are also considered. Graphical abstract: Highlights: Chemical, physical and electrical characteristics of GF enable diverse uses. GF shows reasonably high overpotentials for oxidation and reduction of water. The texture of GF felt can act as a turbulent promoter to enhance mass transport. A high space time yield per pass in electrochemical reactors can be achieved. Applications span energy, electrosynthesis, electrodeposition and water purification.